Fetal programming and Wilms tumor. Issue 1 (25th September 2018) - Heck, Julia E.; He, Di; Janzen, Carla; Federman, Noah; Olsen, Jorn; Ritz, Beate; Hansen, Johnni
Abstract: Background: The "fetal programming" hypothesis has been evaluated in many adult diseases including cancer, but not for Wilms tumor. Wilms tumor has been related to high birthweight, but little is known about other growth metrics such as a baby's birth length, ponderal index, or placenta size, which can shed additional light on growth patterns. Methods: Cases of Wilms tumor ( N = 217) were taken from the Danish Cancer Registry, and controls ( N = 4340) were randomly selected from the Population Register and matched to cases by sex and age. Linkage to the Medical Births Registry provided information on gestational factors and fetal growth measurements, while linkage to the Patient Register provided information on maternal and child health conditions. Results: Despite having typically normal to higher birthweights, Wilms tumor cases had smaller placentas (≤540 g; odds ratio (OR) = 4.24; 95% confidence interval (CI), 1.84–9.78) and a lower placenta‐to‐birthweight ratio (OR = 1.81; 95% CI, 1.17–2.82, per 1 SD decrease). Small placentas were more common among Wilms cases without congenital anomalies (OR = 6.43; 95% CI, 1.95–21.21). Wilms tumor cases had a higher prevalence of high birthweight (>4000 g; OR = 1.57; 95% CI, 1.11–2.22), birth length 55 cm or longer (OR = 1.74; 95% CI, 1.09–2.78), and being large for gestational age (OR = 1.79; 95% CI, 1.08–2.96). Conclusions: Our study corroborates earlier studies showing associations with high birthweight and suggests associations between Wilms tumor and decreased placental size and low placenta‐to‐birthweight ratio.